(untitled) (Journal of Recent Advances in Applied Sciences (pISSN 0970-1990), 2026)
Introduction: Inguinal hernia repair is among the most commonly performed surgical procedures worldwide. The Lichtenstein tension-free mesh repair is the standard approach, though modifications have been introduced to reduce postoperative complications, chronic pain, and recurrence. Aim & Objective: This study aimed to compare the outcomes of the Modified Lichtenstein (ML) technique with the standard Lichtenstein (L) technique regarding postoperative complications, pain, and recurrence in patients undergoing open inguinal hernia repair. Materials & Methods: A prospective comparative study was conducted at the Department of Surgery, J.A. Group of Hospitals, G.R. Medical College, Gwalior. Seventy adult patients with inguinal hernia were randomly assigned to two groups: Group L (n=35) underwent standard Lichtenstein repair, and Group ML (n=35) underwent the Modified Lichtenstein repair. Demographic data, hernia type and side, intraoperative details, postoperative complications, pain scores, and recurrence were recorded and analyzed. Results: Both groups were comparable in age, gender, occupation, hernia type, and side, with most patients’ male (97.1%), aged 41–50 years (27.1%), right-sided hernia (55.7%), and indirect type (82.9%). All cases used spinal anesthesia and polypropylene mesh. Group L had significantly higher wound gaping (31.4% vs 5.7%, p=0.0118) and postoperative discharge (17.1% vs 0%, p<0.05). Seroma occurred in 11.4% of Group L and none in Group ML (p=0.1142). Mild pain predominated in Group ML at 24 and 48 hours, while moderate pain was more frequent in Group L. Recurrence at 11 months was observed in 17.1% of Group L and none in Group ML (p=0.0267). Conclusion: The Modified Lichtenstein repair is a safe, simple, and effective alternative to the standard technique, offering fewer postoperative complications, better pain control, and reduced short-term recurrence.